Catalytic reaction of carbon dioxide with methane on supported Co/Mo catalysts - Khoshroo Ghazaleh (Proceedings of the International Symposium on Analytical and Environmental Problems, 2021)
In this work the reforming of methane with carbon dioxide has been investigated at 773 K on supported Mo-Co/ Al2O3 catalysts with different loading 1%, 5% and 10 %. of Mo. The catalysts were characterized by XRD and TEM methods before and after the reaction. The results revealed that 10%Co/Al2O3 had the highest conversion of CH4 and CO2 and highest syngas formation rate among the mentioned catalysts. In addition, the mentioned catalysts characterization before and after the reaction showed no differences.